Prospective Patterns of Help-Seeking Behavior Among Military Veterans With Probable Posttraumatic Stress Disorder and Major Depressive Disorder. Issue 12 (December 2018) - Currier, Joseph M.; McCormick, Wesley H.; Carroll, Timothy D.; Sims, Brook M.; Isaak, Steven L.
Abstract : Abstract: This study examined help-seeking behavior from professional, informal, and religious sources in veterans with a probable need for treatment. In total, 93 veterans who screened positive for posttraumatic stress disorder/major depressive disorder completed assessments of help-seeking at two time points spaced apart by 6 months. Less than half (40%) reached out to a mental health professional or physician; only 1 in 10 engaged with providers who specialize in evidence-based therapies to a minimally adequate degree. Although roughly two thirds pursued help from informal sources, less than 10% similarly sought help nine or more times. Veterans with high willingness to seek help from specific sources at baseline were more likely to report sustained engagement in help-seeking behavior along these same lines at follow-up. Assessing veterans' help-seeking intentions may add prognostic value in predicting engagement in services. Veterans may also benefit from tailoring service delivery models according to preferred sources of help in their families and communities.